Effects of early maternal separation on the expression levels of hippocampal and prefrontal cortex genes and pathways in lactating piglets - Zhou, Sitong; Yang, Yue; Cheng, Zheng; Wu, Mengyao; Han, Qi; Zhao, Wenzhong; Liu, Honggui (Frontiers in Molecular Neuroscience, 2023)
Introduction In actual production, due to increased litter size when raising pigs, the management of piglets by split-suckling leads to intermittent neonatal maternal separation (MS). Early lactation is a critical period for the cognitive development of the brain of newborn piglets, and we hypothesized that intermittent MS may affect piglets’ neurodevelopment and cognitive ability. Methods To determine the effects of the MS, we selected hippocampal and prefrontal cortex (PFC) tissues from piglets for the detection of neurodevelopmental or cognitive related indicators, the control group (Con group, n = 6) was established with no MS and an experimental group (MS group, n = 6) was established with MS for 6 h/day. Piglets in the MS group were milk-supplemented during the separation period and all piglets in both treatment groups were weaned at postnatal day (PND) 35. On PND 35, three male piglets from each group were sacrificed for hippocampus and PFC samples used for reference transcriptome sequencing. Following bioinformatics analysis, Gene ontology (GO) enrichment, Kyoto encyclopedia of genes and genomes (KEGG) enrichment analysis, and candidate gene screening and pathway were performed for differentially expressed genes. Results The results showed that a total of 1,632 differential genes were identified in the hippocampus of the MS group, including 1,077 up-regulated differential genes, 555 down-regulated differential genes, and 655 significant GO entries. Analysis of the PFC of the MS group revealed 349 up-regulated genes, 151 down-regulated differential genes, and 584 significant GO entries. Genes associated with neurodevelopment were screened for large fold differences in the hippocampus, and genes associated with cognition were screened for large fold differences in the PFC. Quantitative real-time PCR (qRT-PCR) was used to verify the sequencing data. Western blot (WB) experiments revealed that MS inhibited the neurodevelopment-related WNT signaling pathway in the hippocampus and the cognitive-related PI3K-AKT signaling pathway in the PFC. Discussion Taken together, these findings suggest that intermittent MS may affect some cognitive functions in piglets by damaging hippocampal and PFC genes or pathways.